Exploring the Causal Link Between Plasma Lipidome and Trigeminal Neuralgia Using Bidirectional Mendelian Randomization - Yuhang Peng; Xiaolin Zhang; Jinhua Guo; Mingxin Chen; Yuan Cheng; Jianhe Yue; Yongxiang Jiang (Pain Research and Management)
Conclusions: This MR study establishes causal links between specific plasma lipidomes and TN risk, identifying protective lipid species and revealing a bidirectional relationship for PC, offering potential therapeutic targets for TN management.